PEMANTAUAN HIDROGRAFI DAN KUALITAS AIR DI TELUK HURUN LAMPUNG DAN TELUK JAKARTA - Arif Dwi Santoso (Jurnal Teknologi Lingkungan, 2005)
The present study, which was performed in Hurun Bay Lampung and Jakarta Bay, Indonesia, aimed to present the similar method using digital device Chlorotec, type AAQ1183, Alec Electronics for describing the characteristics of tropical coastal hydrography and water quality. The reason of selecting these two locations was to obtain a representation of different dissolved oxygen, temperature and turbidity levels. Jakarta Bay receives large amounts of nutrient-enriched waters, Hurun bay Lampung has moderate or small level of nutrient inputs of organic-polluted waters. The advantage of this method is the observation of field study able to hold with simply and accurately.